Effects of small-sided games and high-intensity interval training on aerobic and repeated sprint performance and peripheral muscle oxygenation changes in elite junior basketball players - Delextrat, A.; Gruet, M.; Bieuzen, F. (The Journal of Strength and Conditioning Research, 2018)
The aim of the current study was to compare the effects of 6 weeks of small-sided game (SSG) and high-intensity interval training (HIIT) on aerobic fitness and muscle oxygenation during a repeated sprint (RS) sequence in elite male junior basketball players. Twenty participants (14.3 ± 0.5 years; 176.8 ± 12.5 cm; 74.5 ± 9.8 kg) performed pre- and post-tests interspersed by 6 weeks of SSG or HIIT training. Testing sessions consisted of the 30-15 intermittent fitness test and an RS sequence (2 bouts of 15 seconds). During RS, muscle oxygenation parameters (tissue saturation index [TSI, %], postsprint muscle reoxygenation rate) were measured using near-infrared spectroscopy. The results showed that both training interventions similarly improved maximal aerobic speed (VIFT, 3.4 and 4.1%, respectively, for HIIT and SSG, P < 0.05) as well as RS ability (smaller percentage decrement by 62.5 and 21.6%, respectively, for HIIT and SSG, P < 0.05). Both training interventions also resulted in a greater dTSI during the second sprint (47.8-114%, P < 0.05) and significant improvements in postsprint reoxygenation after both sprints (+23.0 to +107.7%). Finally, the variation in muscle reoxygenation after sprint 1 was significantly associated with improvements in aerobic (dVIFT, r = 0.61, P = 0.008) and anaerobic (d% Dec during RS, r = -0.487, P = 0.028) performances. The current study has observed that SSG and HIIT resulted in similar improvements in aerobic and anaerobic variables and a better muscle oxygenation capacity during RS. Coaches should be aware that both trainings are applicable methodologies to improve in-season aerobic and anaerobic fitness capacities in junior basketball players.